Master of the Masquerade: An Atypical Presentation of Acute Aortic Dissection - Mando, Ramy (Case Rep Cardiol, 2020)
Acute aortic dissection (AAD) is associated with unacceptably high mortality rate. As such, early diagnosis and aggressive management are essential in order to avoid life-threatening complications. Herein, we report an atypical presentation of AAD and clinical sequelae.